Understanding the failure mechanisms of microwave bipolar transistors caused by electrostatic discharge - 刘进 陈永光 谭志良 杨洁 张希军 王振兴 (Journal of semiconductors, 2011)
Electrostatic discharge（ESD） phenomena involve both electrical and thermal effects,and a direct electrostatic discharge to an electronic device is one of the most severe threats to component reliability.Therefore, the electrical and thermal stability of multifinger microwave bipolar transistors（BJTs） under ESD conditions has been investigated theoretically and experimentally.100 samples have been tested for multiple pulses until a failure occurred.Meanwhile,the distributions of electric field,current density and lattice temperature have also been analyzed by use of the two-dimensional device simulation tool Medici.There is a good agreement between the simulated results and failure analysis.In the case of a thermal couple,the avalanche current distribution in the fingers is in general spatially unstable and results in the formation of current crowding effects and crystal defects.The experimental results indicate that a collector-base junction is more sensitive to ESD than an emitter-base junction based on the special device structure.When the ESD level increased to 1.3 kV,the collector-base junction has been burnt out first.The analysis has also demonstrated that ESD failures occur generally by upsetting the breakdown voltage of the dielectric or overheating of the aluminum-silicon eutectic.In addition,fatigue phenomena are observed during ESD testing,with devices that still function after repeated low-intensity ESDs but whose performances have been severely degraded.